A diffusion tensor MRI study of cervical cord damage in benign and secondary progressive multiple sclerosis patients. Issue 1 (21st June 2009) - Benedetti, B; Rocca, M A; Rovaris, M; Caputo, D; Zaffaroni, M; Capra, R; Bertolotto, A; Martinelli, V; Comi, G; Filippi, M
Abstract : Background: Diffusion tensor (DT) MRI enables quantification of the severity of brain and cervical cord pathology in multiple sclerosis (MS). Objective: To investigate DT MRI patterns of cervical cord damage in patients with benign MS (BMS) and secondary progressive MS (SPMS), in order to achieve a better understanding of the mechanisms underlying the development of irreversible disability in MS. Methods: Conventional and DT MRI scans of the cervical cord and brain were acquired from 40 BMS patients, 28 SPMS patients and 18 healthy individuals. Cervical cord and brain mean diffusivity (MD) and fractional anisotropy (FA) maps were created and average MD and FA were calculated. Cross sectional cord area (CSA) was also computed. Results: 37 (92%) BMS patients and all (100%) SPMS patients had macroscopic cervical cord lesions. Compared with healthy individuals, BMS patients had higher average cord MD while SPMS patients had higher average cord MD, lower average cord FA and lower average CSA. Compared with BMS patients, SPMS patients had lower cord average FA and lower average CSA. In MS patients, Expanded Disability Status Scale (EDSS) was correlated with CSA (r = −0.47, p<0.0001), average cord FA (r = −0.37, p = 0.002) and brain T2 lesion volume (LV) (r = 0.34, p = 0.005). A multivariate regression model identified CSA, average cord FA and brain T2 LV as variables independently influencing the EDSS score (r = 0.58, p<0.0001). Conclusions: Cervical cord damage outside focal macroscopic lesions is limited in patients with BMS. The assessment of cord and brain pathology provides complementary information to improve the understanding of disability accumulation in MS.